Drug-induced liver injury: an overview over the most critical compounds. - Björnsson, Einar S (Archives of Toxicology, 2015)
To access publisher's full text version of this article click on the hyperlink at the bottom of the page There has been a substantial interest in drug-induced liver injury (DILI) recently. National Institutes of Health has sponsored a multicenter study in the USA for the last 10 years, which has collected valuable information in this context. Idiosyncratic DILI is like other adverse effects of drugs underestimated and underreported in most epidemiological studies. A recent prospective population-based study from Iceland found a crude incidence of approximately 19 cases per 100,000 and year. Antibiotic is the class of drugs most commonly implicated in patients with DILI. Amoxicillin-clavulanate continues to be the most commonly implicated agent occurring in approximately 1 out of 2,300 users. Drugs with the highest risk of DILI in the Icelandic study were azathioprine and infliximab. Although rare, statin-induced hepatotoxicity has been well documented. Liver injury associated with the use of herbal medicines and dietary supplements seems to be increasing. Information on the documented hepatotoxicity of drugs has recently been made easier by a website available in the public domain: LiverTox ( http://livertox.nlm.nih.gov ). Unfortunately, at the current time, pre-therapy risk assessment for DILI in the individual patient is difficult but previous well-documented hepatotoxicity is usually a contraindication for a subsequent treatment with the same drug.